Transcriptomics of temperature-sensitive R gene-mediated resistance identifies a WAKL10 protein interaction network - Noel, Katherine; Wolf, Ivan R.; Hughes, David; Valente, Guilherme T. [UNESP]; Qi, Aiming; Huang, Yong-Ju; Fitt, Bruce D. L.; Stotz, Henrik U. (Springer Nature, 2024)
Understanding temperature-sensitivity of R gene-mediated resistance against apoplastic pathogens is important for sustainable food production in the face of global warming. Here, we show that resistance of Brassica napus cotyledons against Leptosphaeria maculans was temperature-sensitive in introgression line Topas-Rlm7 but temperature-resilient in Topas-Rlm4. A set of 1,646 host genes was differentially expressed in Topas-Rlm4 and Topas-Rlm7 in response to temperature. Amongst these were three WAKL10 genes, including BnaA07g20220D, representing the temperature-sensitive Rlm7-1 allele and Rlm4. Network analysis identified a WAKL10 protein interaction cluster specifically for Topas-Rlm7 at 25 °C. Diffusion analysis of the Topas-Rlm4 network identified WRKY22 as a putative regulatory target of the ESCRT-III complex-associated protein VPS60.1, which belongs to the WAKL10 protein interaction community. Combined enrichment analysis of gene ontology terms considering gene expression and network data linked vesicle-mediated transport to defence. Thus, dysregulation of effector-triggered defence in Topas-Rlm7 disrupts vesicle-associated resistance against the apoplastic pathogen L. maculans.